Math

posted by .

log(x-2) +log8 (x-4) =log6 (x-1)

  • Math -

    log(x-2) + log(x-4)/log8 = log(x-1)/log6
    log[(x-2)(x-4)^(1/log8)] = log[(x-1)^(1/log6)]

    (x-2)(x-4)^(1/log8) = (x-1)^(1/log6)
    Ya got me.

    Something tells me the problem was not as posted.

  • Math -

    please solve it

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. math

    (6) Which equation is equivalent to 4^-x=8?
  2. math

    Logarithm!!! Select all of the following that are true statements: (a) log(2x) = log(2) + log(x) (b) log(3x) = 3 log(x) (c) log(12y) = 2 log(2) + log(3y) (d) log(5y) = log(20y) – log(4) (e) log(x) = log(5x) – log(5) (f) ln(25) …
  3. math 12

    log6=x and log8=y, determine an expression for log3 in terms of x an y.
  4. math log

    if log6=m and log 5=n, write 7.2 as an expression in m and n Answer is 2m-n Please help me!!
  5. Test prep

    solve: log8(w-6)=2-log8(w+15) note: the 8 is to be little at the bottom right corner of log
  6. Algebra 1

    solve: log8(w-6)=2-log8(w+15) note: the 8 is to be little at the bottom right corner of log
  7. Please help me!!!! maths

    Solve for x: log5(x-2)+log8(x-4) = log6(x-1). I do not have any idea on this topic.
  8. Math

    The problem I have to solve is log with base 2 ^6 multiply by log base 6 ^ 8. I use the change of base formula and got log6/log2 * log8/log6 Which become log6/log2 * log2()^3/ log 6 I'm stuck here thanks.
  9. Algebra 2

    Solve the equation : 8^2x-1 = 16^x+1 i know you have to log both sides log8^2x-1 = log16^x+1 and then you use the exponential rule 2x-1 log8 = x+1 log16 but then i don't know what to do...
  10. Math

    Solve: Log5(x-2) + log8(x-4)= log6(x-1)

More Similar Questions